Interactive mathematics game using kinect - En, Tan Kang (2013)
This document discusses about Interactive Mathematics Game using Kinect. For kindergarten student they may feel boring during their class, so this project is to target them to gain more interest in their study mainly in mathematics subjects. This gesture based mathematics games proposed will have two part, user interface and Kinect gesture. The user interface was created as interesting as possible to attract the kindergarten student’s attentions. The Kinect gesture detects the skeleton movement of the user and process the data to the applications.To develop this system, gesture recognition devices have to be use. There are four gesture recognition devices that available in the market nowadays. After making several analyses on the findings, finally, Kinect was chosen because it has a better gesture recognition ability as compare to others. After the findings, the designing of the system takes place and a Software Development Life Cycle (SDLC) phase was implemented to design and build this system on times and more systematics. So the purpose of this interaction games is to ensure teaching of the kindergarten students to be fun and enjoyable besides learning what they are needed to. This really helps in the study of the kindergarten students. This mproject is target for the kindergarten students to implant the joyful of studying through interaction games for them.